The Influence of Employee Training on Productivity Through Incentive Intervention at PT. Kawasan Industri Wijayakusuma (Persero) - Subandrio, Subandrio; Purwanto, Wahyu; Rudi Alhempi, Raden (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
This study examines the impact of employee training on employee productivity and performance at PT Kawasan Industri Wijayakusuma (Persero), considering the mediating role of incentives. Utilizing a quantitative research design, the study employed a total sampling technique, gathering data from 50 employees. Path analysis was conducted using Smart PLS to evaluate direct and indirect effects. The findings reveal significant direct relationships between and both and Perf, with coefficients of 0.300 and 0.280, respectively. Furthermore, the analysis showed significant indirect effects, with coefficients of 0.180 for and 0.150 for Perf through. These results indicate that effective training enhances productivity and performance not only directly but also indirectly by increasing employee motivation through incentives. The study underscores the necessity of integrating training and incentive systems to maximize organizational outcomes. By fostering a supportive environment for learning and recognition, organizations can improve employee engagement and overall performance.